Seed germination of two Syagrus species native to Brazil - Pivetta, K. F L [UNESP]; Pedrinho, D. R. [UNESP]; Batista, G. S. [UNESP]; Gimenes, R. [UNESP]; Beckmann-Cavalcante, M. Z. (My University, 2013)
Palm species native to Brazil such as Syagrus picrophylla and S. schizophylla have great ornamental value and for this reason are much demanded for use in landscape. Its propagation is by seeds and often presents considerable problems to nursery managers because their seed has a hard and impermeable shell. Temperature is one of the factors that influence the seed germination process; however, the information for these species is scarce. Thus, this work aimed to study the effects of temperature regimes on the germination of S. picrophylla and S. schizophylla seeds and develop some recommendations in which temperature will obtain high rates of seed germination. The experimental design was entirely randomized with six temperatures and four replications of 25 seeds for each species. Germination and germination rate were evaluated. Higher and faster germination of S. picrophylla and S. schizophylla seeds were verified at constant temperature of 30°C and 35°C; and alternated temperature at 25-35°C.
Keywords: Ornamental palm; Propagation; Seeds; Temperature